The Long-Run Effects of Consequential School Accountability - Jonathan Mansfield; David Slichter (Institute of Labor Economics (IZA), 2021)
The rise of high-stakes accountability programs was one of the most noticeable changes in the U.S. education system during the 1990s and early 2000s. We measure the impact of these programs on students' long-run outcomes. We find that exposure to accountability modestly but detectably increased educational attainment – roughly .02 years per year of exposure. Effects on income were positive, but again modest and insignificant in most specifications. Lastly, if accountability had substantial effects on human capital, treated individuals would be expected to sort into occupations requiring greater use of tested (math and literacy) skills, potentially at the expense of non-tested skills. Instead, we find that accountability had virtually no effect on occupational requirements. Our results suggest that accountability was likely net beneficial for students' long-run outcomes, but not transformative.
Keywords: I28; J24; H0; 330; accountability; long-run effects; teacher incentives; teaching to the test